Effects of Occupational Health and Safety Assessment Series Standard and Organizational Learning on Core Competencies Building - Kwegyir-Afful, Ebo (My University, 2015)
This thesis investigates the effects of an occupational health and safety management system and organizational learning to core competencies building; to be precise, OHSAS 18001:2007 and knowledge creation in a typical industrial setup. Theories employed are OHSAS 18001:2007 and the five phase model of organizational knowledge creation process. - Knowledge spiral. Essentially, it employs the Serpentine module of Evolute research tool for enquiry, data collection and analysis of the levels of safety culture and knowledge interaction. Interviews as well as observations to ascertain the extent of applicability of these theories are also presented. Herein suggestions and proposals are given for factors that need improvement through management initiative and direction. The idea is boosting capacity through sustainable employee wellbeing and core competency building programs; - the human factor. In this way, the effects of institutionalizing a vibrant policy as proposed in an industrial environment to productivity of the company can be realized. The writer hopes that by implementing these proposals of the study, there would ultimately be a breakthrough in the dynamic capability of the firm. The case study is a company that has been in existence for almost a century and currently the global leader in provision of thermal processes supplies.
Keywords: occupational health; safety management system; safety culture; organizational learning; dynamic capability; knowledge creation and core competences building.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|